Fabrication of nanocomposites with silica nanoparticles. (2018) - Constantinescu, Dan M.; Apostol, Dragos A.; Picu, Catalin R.; Krawczyk, Krzysztof; Sieberer, Manfred; Hadar, Anton; Feuchter, Michael
Abstract: Functionalization of silica nanoparticles is needed as to improve the mechanical performance of epoxy nanocomposites. Previous experience showed that direct dispersion of commercially available silica nanofillers does not improve significantly the mechanical properties of resulting nanocomposites. Different methods of fabrication are presented along with comments on the possibilities to improve the quality of obtained specimens. Both functionalized and unfunctionalized silica nanoparticles were added in three epoxy resins. The considered filling fraction was in most cases 0.1, 0.3 and 0.5 wt%. The obtained nanocomposites were subjected to monotonic uniaxial loading at room temperature. The static mechanical properties were not significantly changed regardless the filler type or percentage and type of epoxy resin.